Saturable and dispersive parity-time symmetric directional coupler: a transmission-line modelling study - Phang, Sendy; Vukovic, Ana; Benson, Trevor M.; Creagh, Stephen; Sewell, Phillip; Gradoni, Gabriele (2014)
In this paper, numerical modelling of Parity-Time (PT) coupled waveguides is reported. The PT coupled waveguide structure consists of two coupled slab waveguides based on GaAs material with gain/loss material parameter models, including both dispersion and saturation. The numerical model used analyses the impact of dispersion and saturation on the eigenmode extracted by a curve fitting approach. The results show that the presence of saturation may prohibit the appearance of the threshold point above which the PT system becomes unstable.